Health and social services for Francophone seniors in Eastern Ontario and Manitoba: Guidelines to improve the continuity of French language services. Research Report - Summary. - Kubina, Lucy-Ann; de Moissac, Danielle; Savard, Jacinthe; Savard, Sébastien; Giasson, Florette (Groupe de recherche sur la formation et les pratiques en santé et service social en contexte francophone minoritaire (Grefops), 2018)

Les services sociaux et de santé pour les personnes âgées francophones de l’Est ontarien et du Manitoba : lignes directrices pour améliorer la continuité des services en français - Kubina, Lucy-Ann; de Moissac, Danielle; Savard, Jacinthe; Savard, Sébastien; Giasson, Florette (Groupe de recherche sur la formation professionnelle en santé et service social en contexte francophone minoritaire, 2018)

Health and social services for Francophone seniors in Eastern Ontario and Manitoba: Guidelines to improve the continuity of French language services. Research Report. - Kubina, Lucy-Ann; de Moissac, Danielle; Savard, Jacinthe; Savard, Sébastien; Giasson, Florette (Groupe de recherche sur la formation et les pratiques en santé et service social en contexte francophone minoritaire (Grefops), 2018)

Management strategies to improve French language service coordination and continuity for official language Francophone seniors in Canada - de Moissac, Danielle; Savard, Jacinthe; Savard, Sébastien; Giasson, Florette; Kubina, Lucy-Ann (Healthcare Management Forum, 2020)
Evidence suggests that language barriers present obstacles to healthcare access and quality for Francophone seniors in official language minority communities across Canada. Addressing language barriers and providing continuity is challenging, as French language services (FLSs) rely heavily on bilingual providers and the practice of active offer by all staff. This qualitative research used semi-structured group and individual interviews to explore mechanisms supporting FLS coordination and continuity in two Canadian provinces. Identification of the language variable in health records, virtual healthcare, and FLS directories are conducive to FLS continuity, but financial and resource limitations present major obstacles. Management strategies to facilitate continuity of FLS across health organizations are discussed.

Strategies to improve French language health and social service continuity for seniors in Ontario and Manitoba - Savard, Jacinthe; Savard, Sébastien; de Moissac, Danielle; Giasson, Florette; Kubina, Lucy-Ann (Linguistic Minorities and Society, 2021)
Access to health and social services in one’s official language of choice is an important component of quality and safety of care for seniors. Access can be fragmented, even in the context of legislation guaranteeing the right to receive such services, and in areas with a higher proportion of bilingual providers. Using a community-based participatory approach, we identified mechanisms promoting or impeding the clinical integration of health and social French language services intended for seniors living in two Canadian Francophone minority communities. Thirteen recommendations highlight the possibility for new initiatives to promote a continuum of French language health and social services in a minority context, involving collaboration among a variety of actors at all levels of our analytical framework: service trajectory (providers); francophone communities; organizational; political and regulatory; and symbolic (values) structures. Keywords: seniors, linguistic minorities, service integration, health and social services, continuity of care

Les services sociaux et de santé pour les personnes âgées francophones de l’Est ontarien et du Manitoba : lignes directrices pour améliorer la continuité des services en français. Rapport de recherche - Résumé. - Kubina, Lucy-Ann; de Moissac, Danielle; Savard, Jacinthe; Savard, Sébastien; Giasson, Florette (Groupe de recherche sur la formation professionnelle en santé et service social en contexte francophone minoritaire, 2018)

Le recrutement et la rétention des professionnels de la santé et des services sociaux bilingues en situation minoritaire - de Moissac, Danielle; Savard, Sébastien; Ba, Halimatou; Zellama, Faïçal; Benoît, Josée; Giasson, Florette; Drolet, Marie (Université de Saint-Boniface et Université d'Ottawa, 2014)
Cete étude cherchait à connaitre les éléments favorisant l’engagement et la motivation des professionnels ainsi que les pratiques de gestion des ressources humaines qui encourage le personnel bilingue à s’intéresser au travail en milieu bilingue et à demeurer en poste.

Prolonged Impact of the COVID-19 Pandemic on the Well-being and Roles of Family/Friend Caregivers of Older Adults Living at Home in Canadian Official Language Minority or Majority Communities - Savard, Jacinthe; Savard, Sébastien; Duong, Patrick; Hatungimana, Nelly Oriane; Benoit, Josée; De Moissac, Danielle; Dupuis-Blanchard, Suzanne; Robitaille, Annie (Canadian Journal on Aging / La Revue canadienne du vieillissement, 2026)
Résumé Contexte. Des études menées pendant la pandémie de COVID-19 soulignent que le confinement a réduit l’accès aux services et accru les responsabilités et l’isolement des proches aidants. Objectif. Cette étude examine les répercussions à long terme chez 83 proches aidants de personnes âgées provenant de quatre provinces canadiennes. Méthodes. Les participants ont rempli un questionnaire en ligne entre octobre 2021 et février 2022, puis à nouveau six mois plus tard, sur l’aide fournie, le soutien reçu, la langue des services et le bien-être psychologique. De plus, huit aidants ont participé à une entrevue qualitative. Résultats. La plupart des services d’aide à domicile ont été maintenus pendant la pandémie, certains avec un personnel réduit, à l’exception des services de répit et de transport. Les aidants ont accru leur aide pendant les confinements, et cette implication accrue s’est poursuivie en 2022. Ils ont perçu un impact négatif de la pandémie sur leur santé et celle de la personne aidée. Les participants issus de communautés linguistiques minoritaires officielles ont décrit des difficultés supplémentaires pour accéder aux services dans leur langue préférée. Discussion. Une meilleure reconnaissance des besoins des aidants contribuera à soutenir leur rôle en tant que partenaires au sein des organismes de santé. Abstract Background. Studies conducted during the COVID-19 pandemic highlighted that confinement reduced access to services and increased caregivers’ responsibilities and isolation. Objectives. This study examines the longer-term impacts among 83 unpaid caregivers of older adults from four Canadian provinces. Methods. Participants completed an online questionnaire between October 2021 and February 2022, and again 6 months later, on the assistance provided, support received, language of services, and psychological well-being. Additionally, eight caregivers participated in a qualitative interview. Findings. Most home support services were maintained during the pandemic – some with restricted staffing – except for respite and transportation services. Caregivers increased their assistance during the lockdowns, and this higher involvement persisted in 2022. They perceived a negative impact of the pandemic on their health and that of the care recipient. Participants from official language minority communities described additional challenges accessing services in their preferred language. Discussion. Greater recognition of caregivers’ needs will help support their role as partners within health organizations.

Recruitment and retention of bilingual health and social service professionals in Francophone minority communities in Winnipeg and Ottawa - Savard, Sébastien; de Moissac, Danielle; Benoît, Josée; Ba, Halimatou; Zellama, F.; Giasson, Florette; Drolet, Marie (Accessibility and active offer: Health care and social services in linguistic minority communities, 2017)
The difficulty in recruiting and retaining employees able to work in both official languages has been identified as one of the most significant reasons why Francophone seniors in minority language communities are unable to access social services and health care in French. This chapter presents the findings of a study of 55 profes sionals interviewed in six focus groups, who worked in bilingual organizations in one of the two regions studied (Winnipeg, Manitoba and Ottawa, Ontario). We hoped to identify the factors that led these employees to work in bilingual organizations and those that had encouraged them to stay in the organizations where they worked. Our findings show that the desire to contribute to the well-being of Francophones and the opportunity to obtain stable positions offering good working conditions are among the most important recruitment factors. The quality of the work environment and the opportunity to work in a diverse and inclusive workplace are retention factors mentioned regularly by the study participants. A greater recognition of the additional workload associated with working in both languages, and the recruitment of senior bilingual management staff, are among the recommendations proposed to improve the recruitment and retention of bilingual staff. Key Words: Recruitment and retention, social service and health professionals, Francophones in minority language communities.

Le recrutement et la rétention d’intervenants en santé et services sociaux bilingues en situation francophone minoritaire à Winnipeg et à Ottawa - Savard, Sébastien; de Moissac, Danielle; Benoît, Josée; Ba, Halimatou; Zellama, Faïçal; Giasson, Florette; Drolet, Marie (Accessibilité et offre active : Santé et services sociaux en contexte linguistique minoritaire, 2017)
La difficulté à recruter des professionnels en mesure d’intervenir dans les deux langues officielles a été mentionnée comme une des causes les plus importantes du manque d’accès à des services sociaux et de santé en français pour les personnes âgées francophones en situation minoritaire. Ce chapitre présente les résultats d’une recherche réalisée auprès de 55 intervenants, rencontrés dans six groupes de discussion et travaillant dans des organisations bilingues dans deux régions, soit Winnipeg au Manitoba et Ottawa en Ontario. Nous voulions connaître les facteurs ayant incité ces intervenants à vouloir travailler dans des organisations bilingues et ceux favorisant leur rétention dans les organismes où ils travaillent. Les résultats démontrent que la volonté de contribuer au mieux-être des francophones et la possibilité d’obtenir des postes stables offrant des conditions de travail intéressantes font partie des facteurs de recrutement les plus importants. La qualité du climat de travail et la possibilité de travailler dans un milieu caractérisé par la diversité sont des facteurs de rétention mentionnés régulièrement par les participants à l’étude. Une meilleure reconnaissance du fardeau supplémentaire associé au fait de travailler dans les deux langues et le recrutement de cadres bilingues font partie de recommandations permettant de faciliter le recrutement et la rétention de personnel bilingue. Mots-clés : recrutement et rétention, intervenants services sociaux et de santé, francophones en situation minoritaire.